A single amino acid change in the Plasmodium falciparum RH5 (PfRH5) human RBC binding sequence modifies its structure and determines species-specific binding activity (2012)
Identifying the ligands or regions derived from them which parasites use to invade their target cells has proved to be an excellent strategy for identifying targets for vaccine development. Members of the reticulocyte-binding homologue family (P. fRH), including RH5, have been implicated in invasion as adhesins binding to specific receptors on erythrocyte surface. The regions mediating P. fRH5-RBC specific interactions have been identified here by fine mapping the whole P. fRH5 protein sequence. These regions, called high activity binding peptides (HABPs), bind to a receptor which is sensitive to trypsin treatment and inhibit merozoite invasion of RBCs by up to 80%, as has been found for HABP 36727. Our results show that a single amino acid change in the HABP 36727 sequence modifies a peptide's 3D structure, thereby resulting in a loss of specific binding to human RBCs and its inhibition ability, while binding to Aotus RBC remains unmodified. Such invasion differences and binding ability produced by replacing a single amino acid in an essential molecule, such as P. fRH5, highlight the inherent difficulties associated with developing a fully effective vaccine against malaria. © 2011 Elsevier Ltd.